Genetic parameters and selection of biofortified lettuce genotypes based on selection indices - Sousa,Luciana A. de (2021)
ABSTRACT Obtaining biofortified vegetables with an emphasis on lettuce is a tool to improve the nutritional status of the population. Selection indices can maximize the simultaneous selection of good agronomic traits and high carotenoid levels. The objective of this study was to estimate the genetic parameters and efficiency of different indices in selecting genotypes of biofortified lettuce with high concentrations of carotenoids and favorable agronomic traits. Statistical analyses were performed on 91 genotypes belonging to the vegetable germplasm bank of the Federal University of Uberlândia, Brazil. The variables analyzed were the chlorophyll index of the leaves, plant diameter, stem diameter, and number of leaves per plant. The values found for narrow sense heritability (h²) ranged from 89.63% (stem diameter) to 96.05% (chlorophyll), showing a high magnitude. The Smith-Hazel index, sum of ranks by the Mulamba & Mock index, direct and indirect selection, and Williams base index were used to predict the selection gains. A total of 17 individuals were selected using the selection methodologies. The Smith-Hazel, Williams, and Mulamba & Mock indices were efficient in showing good direct gains for the evaluated traits. Thirteen genotypes were selected for all indices presenting suitable agronomic traits, which show promise for advancing generations within the breeding program to obtain biofortified lettuce strains.